Organizational development and alignment : the tensegrity mandala framework - Singh, Gagandeep (SAGE Publications, 2013)
Organizational Development and Alignment: The Tensegrity Mandala Framework takes a close look at the underlying axioms of Organization Design and Alignment that have not only proliferated rigid structures and oppressive hierarchies, but also have rendered employees worldwide as mere instruments and dehumanized the organizational context.